2022
DOI: 10.3390/foods11162527
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Metabolomic and Transcriptomic Analysis Reveals Differential Flavonoid Accumulation and Its Underlying Mechanism in Fruits of Distinct Canarium album Cultivars

Abstract: Canarium album fruit has great potential to be consumed as a raw material not only for food but also medicine. The diverse active metabolites composition and content of C. album fruits greatly affect their pharmacological effects. However, up to now, there has been no report on the global metabolome differences among fruits from distinct C. album cultivars. In our present study, by using non-targeted metabolomics techniques, we identified 87 DAMs (differentially accumulated metabolites) including 17 types of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The genes associated with flavonoid biosynthesis are mainly classified into structural and regulatory genes [41]for instance, CHS, FLS, F3H, F3 H, C4H, etc. C4H plays an important role in flavonoid biosynthesis [42][43][44]. Correlation analysis showed that C4H at all three ripening stages positively regulated flavonoids including luteolin, hesperetin, homoeriodictyol, phloretin, butin, aromadendrin, naringenin chalcone, and pinobanksin.…”
Section: Discussionmentioning
confidence: 98%
“…The genes associated with flavonoid biosynthesis are mainly classified into structural and regulatory genes [41]for instance, CHS, FLS, F3H, F3 H, C4H, etc. C4H plays an important role in flavonoid biosynthesis [42][43][44]. Correlation analysis showed that C4H at all three ripening stages positively regulated flavonoids including luteolin, hesperetin, homoeriodictyol, phloretin, butin, aromadendrin, naringenin chalcone, and pinobanksin.…”
Section: Discussionmentioning
confidence: 98%
“…The “Tan xiang” cultivar exhibited significantly higher levels of flavones, flavanols, and their derivatives than the other two cultivars ( p < 0.05). Although genistin was detected ( 8 ), its limited quantity precluded quantification.…”
Section: Resultsmentioning
confidence: 99%
“…As one of the 110 medicinal foods in China, Chinese olive contains higher free phenolic levels (300 mg/100 g fresh weight) than grapes, apples, pears, and other fruits and also ranks first among 68 Chinese medicinal materials in terms of phenolic content ( 6 ). Despite being rich in FPs ( 7 , 8 ), there is a paucity of studies comparing the PCs profiles of different Chinese olive cultivars, especially the bound phenolic fraction.…”
Section: Introductionmentioning
confidence: 99%
“…To date, transcriptomic techniques have been successfully applied in C. album [64][65][66], and the chloroplast genome with a 163,140 bp of C. album has been reported [67], the comprehensive genomic and full-length transcriptomic information is still poorly understood. The importance of fruit quality and the exceptional bioactive properties in C. album have long been recognized; hence, we constructed a full-length transcriptome of C. album by using PacBio Sequel and Illumina RNA-seq here to increase our understanding of the vital and dynamic process of C. album fruit development.…”
Section: Rt-qpcr For Validation Of Rna-seqmentioning
confidence: 99%